Covalent‐Induced Heterostructure of Covalent‐Organic Frameworks and MXene as Advanced Electrodes with Motivated Pseudocapacitance Performance - Geng, Qianhao; Wang, Haichao; Wu, Yang; Lv, Li‐Ping; Chen, Shuangqiang; Sun, Weiwei; Wang, Yong (ChemElectroChem, 2022)
Heterostructures based on covalent organic frameworks (COFs) and conductive materials have attracted more attentions to effectively apply COF‐related materials for supercapacitor. Here, the as‐prepared amino‐modified Ti3C2 MXene nanosheets are adopted to support the in‐situ growth of anthraquinone‐based COFs (AQ‐COF) to fabricate the heterostructures of COFs uniformly dispersed on surface of MXene, based on the covalent interaction between terminal C=O groups of COFs and amino units of MXene. Besides, the morphology and porous structures of COF@MXene heterostructures are optimized by controlling the amounts of MXene nanosheets. Combining the superiority from the two‐dimensional structure with high conductivity of MXene and porous structure with abundant redox‐active groups inherited from AQ‐COF, the COF@MXene‐15 heterostructure electrode delivers large surface area with optimal porous structures, leading to the maximally‐activated C=O units for charge‐storage and capacitance‐controlled electrochemical kinetics. Improved specific capacitance (290 F g−1 at 0.5 A g−1) and rate capability can be achieved for the COF@MXene‐15 heterostructure as the electrode for supercapacitor in Na2SO4 electrolyte. It is the first time to report the heterostructure of COFs and MXene as the electrode for supercapacitor, and this work would promote further application of COFs and related materials for other energy‐storage systems. COFs combined with MXene: The strategy of anthraquinone‐based covalent organic frameworks (AQ‐COF) in‐situ grown on amino‐modified Ti3C2 MXene nanosheets through covalent interaction is adopted to construct a series of porous COF@MXene heterostructures with improved electrochemical performance as electrodes for high‐performance supercapacitor.